CD36 Is Significantly Correlated with Adipophilin in Human Carotid Lesions and Inversely Correlated with Plasma ApoAI - Sophie Collot-Teixeira (Journal of Biomedicine and Biotechnology, 2008)
OxLDL uptake and cholesterol efflux inhibition in macrophages play a key role in atherosclerotic plaque formation, rupture, and thrombotic ischemia. This study investigates genes implicated in OxLDL uptake (CD36, SRA), cholesterol efflux inhibition (adipophilin, ADFP), and inflammatory recruitments of leukocytes (IL-8) in plaque lesion areas (PLAs) compared to nonplaque lesion areas NPLAs) in human carotid endarterectomy specimens. Gene and protein expressions were assayed using quantitative PCR and quantitative immunohistochemistry. Pearson tests were used to investigate potential correlation between (a) different gene expressions and (b) gene expression and patient's plasma constituents. CD36, SRA, ADFP, and IL-8 were shown to be significantly more expressed in PLA compared to NPLA. In PLA, a significant correlation was observed between CD36, SRA, ADFP, and IL-8 mRNA levels. Moreover, CD36 expression level was significantly inversely correlated to plasma marker ApoAI. The above investigated genes/proteins may play a key role in the maturation of atherosclerotic lesions.